(untitled) (Journal of Dhaka Medical College, 2017)
Introduction: Premature rupture of membrane or PROM means when membrane ruptures before the onset of labour at a gestational age less than 37 completed weeks. In Bangladesh, every year, around 28,000 women die due to complications of pregnancy and childbirth. Nonscientific intervention in PROM made at various levels intensify the pregnancy complications several times, thereby leading many more deaths of foetus and newborn. Aetiology of PROM is largely unknown. The possible causes are either reduction of membrane strength or an increase in intrauterine pressure or both. Proper diagnostic facilities, proper monitoring and standard protocol in the management can improve the maternal and fetal outcome. Aim and objective: The aim of the study was to observe the incidence, type and maternal and fetal outcome of PROM. Materials and Method: A prospective case control analytical study was carried out at Dhaka Medical College Hospital, Dhaka from May 2000 to December2000. Total 120 patients were selected for this study among them 60 patients as case (Group A) and 60 patients were taken as control (Group B). Both primi and multigravida with Pregnancy more than 28 weeks with intact membrane as control and spontaneous rupture of membrane taken as case. High- risk patients such as hypertensive disorder of pregnancy, APH, cardiac disease, previous H/O caesarean section were excluded from the study. After taking proper history, speculum examination, some diagnostic investigations were carried out. Findings were recorded in predesigned questionnaire and statistical analysis were done using computerized software SPSS for Windows. A P value < 0.05 was taken as significant. Results: In our study maternal complications were significantly higher in Group A patients (Chi-square test: X2 = 6.263, df= 1, P< 0.05). Number of premature babies in PROM patients (25%) was significantly higher than control group. Perinatal morbidity was found higher in PROM (36.66%) compared to control group (31.66%). Most common morbidity was neonatal jaundice in PROM patients (13.33%) compared to babies of control group (8.33%). Conclusion: This study focused on certain risk factors in relation to PROM which can be preventable and reduce incidence and improvement of maternal and fetal outcome. J Dhaka Medical College, Vol. 25, No.2, October, 2016, Page 82-86